1999
DOI: 10.4141/a99-003
|View full text |Cite
|
Sign up to set email alerts
|

Variability of apparent ileal amino acid digestibility in different pea samples for growing-finishing pigs

Abstract: Variability of apparent ileal amino acid digestibility in different pea samples for growing-finishing pigs. Can J. Anim. Sci. 79: 467-475. Six barrows, average initial body weight 32.5 kg, fitted with a simple T-cannula at the distal ileum, were used to investigate factors responsible for the variability of apparent ileal amino acid (AA) digestibility values among six pea samples. The barrows were fed six corn-starch-based diets, formulated to contain 16.5% crude protein (CP) (as-fed) from six different pea sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 37 publications
3
12
2
Order By: Relevance
“…In contrast, De Coca-Sinova et al (2008) reported a Pearson correlation coefficient of-0.745 (P< 0.001) between NDF and CAID for Lys in a study with six SBM samples. Similar results have been reported by Fan and Sauer (1999) in peas (n = 6). Mateos et al (2011) documented that SBM from BRA contained more NDF but also more CP than SBM from USA and ARG.…”
Section: Coefficients Ofapparent and Standardized Tíeal Digestibtíitysupporting
confidence: 91%
“…In contrast, De Coca-Sinova et al (2008) reported a Pearson correlation coefficient of-0.745 (P< 0.001) between NDF and CAID for Lys in a study with six SBM samples. Similar results have been reported by Fan and Sauer (1999) in peas (n = 6). Mateos et al (2011) documented that SBM from BRA contained more NDF but also more CP than SBM from USA and ARG.…”
Section: Coefficients Ofapparent and Standardized Tíeal Digestibtíitysupporting
confidence: 91%
“…The reason for the lower fecal P contents in diets 4 and 5 (3.37-4.29%) than those of diets 1-3 (2.75-2.97%) was not clear, as the dietary supplementation of sodium monobasic phosphate, a very digestible source of P, was progressively increased from diets 1 to 5. The possible reason may be the low P digestibility value in peas, and that the inclusion of pea per se inhibited the digestive utilization of P because of the presence of anti-nutritive factors including trypsin inhibitors and lectins in peas (Begbie and Pusztai 1989;Fan and Sauer 1999). These anti-nutritive factors may affect the digestive utilization of P through two possible mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Second, Radley peas used in this study was generally high in anti-nutritive factors including trypsin inhibitors and lectins (Begbie and Pusztai 1989;Fan and Sauer 1999). As discussed in the previous section, the presence of these anti-nutritive factors might have adversely affected the digestion and absorption of phosphates associated with pea proteins, DNA and RNA, and indirectly increased the level of the endogenous P in the ileal and fecal samples, thus resulting in relatively low and even negative P digestibility values in peas.…”
Section: Resultsmentioning
confidence: 99%
“…As discussed by Gatel (1992), differences in processing conditions, antinutritional factors and other factors associated with variety and growing conditions were only, in part, responsible for the large variation. Fan and Sauer (1999) recently determined the ileal amino acid digestibility values in six samples of peas which originated from various locations in western-Canada. Of the indispensable (+ semi-) amino acids within each sample, the ileal digestibility values of arginine and lysine were relatively high, ranging from 88.3 to 91.3% and from 78.7 to 85.2%, respectively, while the digestibility values of cysteine, methionine and tryptophan were relatively low, ranging from 53.8 to 62.7%, 69.4 to 75.4%, and from 53.1 to 70.4%, respectively.…”
Section: Legume Seedsmentioning
confidence: 99%